Transplantasi Organ Tubuh Manusia Dalam Perspektif Hukum Positif Indonesia: Transplantasi Organ Tubuh Manusia Dalam Perspektif Hukum Positif Indonesia - Michelle Angelika S; Yohanes Firmansyah; Yana Sylvana; Hanna Wijaya (Jurnal Medika Hutama, 2021)
Transplantation is the transfer of all or part of the body's organ tissue from a donor to a donor recipient with the hope of improving the quality of life. In Indonesia, organ transplantation has not been clearly regulated. The need for organ donation is increasing from year to year compared to available organs, according to data reported to the Global Observatory on Donation and Transplantation (GODT), an analysis of 2010 transplant activity for 95 countries, representing nearly 90% of the world's population of organ transplant activities. an increase of 2.12% during 2009, but it is estimated that this is still far from the global demand. This creates lucrative business opportunities for irresponsible individuals. Therefore, good governance is a must to create excellent service to the community.